Supplementation with live yeast increases rate and extent of in vitro fermentation of nondigested feed ingredients by fecal microbiota. (23rd February 2019) - Kiros, Tadele G; Agyekum, Atta Kofi; Wang, Jing; D'Inca, Romain; Beaulieu, Denise A; Auclair, Eric; Van Kessel, Andrew G
Abstract: Two studies were conducted to investigate the effect of live yeast (LY ) on the in vitro fermentation characteristics of wheat, barley, corn, soybean meal (SBM ), canola meal, and distillers dried grains with solubles (DDGS ). In Study 1, LY yeast was added directly to in vitro fermentations inoculated with feces from lactating sows, whereas as in study 2, feces collected from lactating sows fed LY as a daily supplement was used. Selected feedstuffs were digested and the residue added to separate replicated ( n = 3) fermentation reactions. Study 1 was conducted in two blocks, whereas study 2 was conducted using feces collected after a period of 3 (Exp. 1) or 4 wk (Exp. 2) of LY supplementation. Accumulated gas produced over 72 h was modeled for each substrate and the kinetics parameters compared between LY and control groups. The molar ratio of the volatile fatty acids (VFAs ) produced in vitro were also compared at 12 and 72 h of incubation. In study 1, in vitro addition of yeast increased ( P < 0.001) the rate of gas production ( R max ). However, a yeast × substrate effect ( P < 0.05) observed for total gas accumulated ( A ), time to half asymptote ( B ), and time required to reach maximum rate of fermentation ( T max ) suggested that yeast-mediated increases in extent and rate of fermentation varied by substrate. Greater total gas production was observed only for corn and SBM, associated with greater B and T max . Supplementation with LY appeared to increase A and R max although with variation between experiments and substrates. In Exp. 1, LY decreased ( P < 0.05) B and T max . However, a yeast × substrate effect ( P < 0.05) was observed for only A (for wheat, barley, corn, and corn DDGS) and R max (wheat, barley, corn, and wheat DDGS). In Exp. 2, LY increased ( P < 0.0001) A and decreased B . However, an interaction ( P < 0.05) with substrates was observed for R max (except SBM) and T max . With exception of the DDGS samples, LY supplementation increased ( P < 0.05) VFA production at 12 and 72 h of incubation. Yeast increased ( P < 0.05) the molar ratios of acetic acid and branch-chain fatty acids at 12 h of incubation; however, this response was more variable by substrate at 72 h. In conclusion, LY supplementation increased the rate and extent of in vitro fermentation of a variety of substrates prepared from common feedstuffs. Greater effects were observed when LY was fed to sows than added directly in vitro, suggesting effects on fermentation were not mediated directly.